2021
DOI: 10.34172/ijer.2021.24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Modalities for SARS-Cov-2: A Review Study

Abstract: Background and aims: In late December 2019, a cluster of progressive pneumonia-like respiratory syndromes broke out in Wuhan, China. As the number of cases continued to rise, the 2019 coronavirus disease (COVID-19) has been declared a global public health emergency. The causative agent, i.e., SARS-CoV-2, is a highly contagious strain, which has resulted in the rapid worldwide outbreak of COVID-19. COVID-19 is an overwhelmingly transmissible disease that requires early and accurate diagnosis for proper and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The Coronavirus can target the upper and lower respiratory tract and cause disease with a wide range of clinical manifestations from asymptomatic to critical conditions in infected individuals. Interestingly, COVID‐19 has no specific clinical symptoms compared to common viral respiratory diseases (Sheervalilou, Ahmadzadeh et al., 2021 ; Sheervalilou et al., 2022 ). Studies have shown that old age and having the underlying disease (some morbidity) are related to the severity of COVID‐19 (Heidari Nia et al., 2022 ; Sargazi et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Coronavirus can target the upper and lower respiratory tract and cause disease with a wide range of clinical manifestations from asymptomatic to critical conditions in infected individuals. Interestingly, COVID‐19 has no specific clinical symptoms compared to common viral respiratory diseases (Sheervalilou, Ahmadzadeh et al., 2021 ; Sheervalilou et al., 2022 ). Studies have shown that old age and having the underlying disease (some morbidity) are related to the severity of COVID‐19 (Heidari Nia et al., 2022 ; Sargazi et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, there is no definite treatment to stop SARS‐CoV‐2 replication (Sheervalilou et al, 2021 ). Interestingly, molecular docking and structural dynamics experiments have shown that a variety of bioactive compounds (Bhardwaj et al, 2021 ; Bhardwaj et al, 2021a , 2021b ; Sharma et al, 2021 ) or chemically synthesized (Bhardwaj et al, 2021 ) or turmeric‐derived (Singh, Bhardwaj & Purohit, 2021 ) compounds with good docking scores could bind to different proteins of the virus, and therefore, phonetically inhibit its replication (Singh, Bhardwaj, Das et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%